Analysis of Mobile Agents using Invariants of Object Nets - Köhler-Bußmeier, Michael; Moldt, Daniel (Electronic Communications of the EASST, 2009)
Mobility induces new challenges for dynamic systems, which need a new conceptional treatment: systems, that deal for example with mobile agents, need extended security concepts to handle the risks, induced by foreign, untrusted agents. In this contribution we use object nets to model mobile systems. Object nets are Petri nets which have Petri nets as tokens – an approach known as the nets-withinnets paradigm. Object nets are called elementary if the net system has a two levelled structure. In this work we apply structural analysis methods for object nets – namely place invariants – to a simple case study modelling mobile agents.